Effect of Spice Drinks (Red Ginger and Cinnamon) on Dysmenorrhea Pain - Ni Gusti Made Ayu Agung Budhi; Aticeh; Willa Follona; Yetri Elisya (GoAcademica Research & Publishing, 2022)
Menstrual pain is called dysmenorrhea; 15% of women who experience menstrual pain feel uncomfortable. Savitri & Swari (2020) stated that menstrual pain occurs 1-2 days before menstruation appears and continues until the third day of menstruation or the end. Some studies declare that ginger water decoction can reduce menstrual pain or dysmenorrhea. In vitro and in vivo, ginger has been shown to have antimicrobial, antifungal, anthelmintic, antioxidant, anti-inflammatory, antitumor, immunomodulatory, antilipidemic, analgesic properties, and protective effects on the digestive tract. Likewise, cinnamon and cloves can relieve toothache. This research method uses a quasi-experimental design with control by giving ginger and cinnamon spice drinks. The population of this study was women aged 19-21 years who experienced menstrual pain with a large sample of the results of the calculation of the average difference test in two pairs of groups, which were 30 respondents in each group, both intervention, and control. The study found that a spiced drink consisting of red ginger, cloves, and cinnamon and given honey positively affected menstrual pain (dysmenorrhea) with the p-value. There is an effect of a spiced drink consisting of red ginger, cloves, and cinnamon and given honey on menstrual pain (dysmenorrhea).